PESANTREN DAN BAHASA ARAB - ISMAIL BAHARUDDIN (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2014)
Boarding school is the oldest place of learning in Indonesia , boarding schools are very active role in the print easy cadres potential and have a high enough skill , although boarding is more synonymous with learning the science of religion , but the students do not lose competitiveness with non-  boarding students . In general, even in boarding schools often once every day in suguhi with Arabic or Arabic books which are usually referred to as the yellow book , the yellow book would never have found the Latin writing , only writing in Arabic without harokat . In this case the students are required by the chaplain to understand what is covered in the book , therefore, obliged to any students proficient in Arabic.Arabic in a boarding school not only in the yellow book alone , in the learning process of the students at the school diniyah still having Arabic. Moreover, the cottage salafi like Langitan, roommate and so forth , Arabic became the language yaumiyyah or colloquialisms. And for students who scored proficient in Arabic , not a way that made by the caregivers as Indonesian songs translates into Arabic, from English to Arabic, even the students memorize mufrodat to increase vocabulary. In learning activities at the school or at the school diniah , most subjects in priority is nahwu shorof lesson which is the first step to mastering the rules of the Arabic language , and to subsequently enjoined the students to memorize nadhom  -  nadhom or poems related to peljaran Arabic, among nadhom  -  nadhom it is :  nadhom Maqsud , Alfiyah ibn malik , qowaidul i'lal, tashrifiyah , imrithi and so on.